Does Strategic Agility Manifest in the Performance of Real Estate Firms in Nairobi County? An Empirical Investigation - Ndegwa, Catherine; Kiilu, Peter (European Journal of Business and Strategic Management, 2025)
Purpose: This study explores the challenges affecting the performance of real estate firms in Kenya, with a particular emphasis on the role of strategic agility in influencing organizational outcomes. Methodology: The study was guided by positivism research philosophy. It employed a descriptive cross-sectional design and targeted a census of eighty-three (83) real estate firms operating in Nairobi County, Kenya. Data was collected using a 5-point Likert scale, and ordinary least squares (OLS) regression was utilized to estimate and analyze the data. Findings: The findings revealed a significant positive relationship between strategic agility and organizational performance. The study demonstrated that the effective alignment of strategic agility enhances the performance of real estate firms by enabling them to navigate dynamic market conditions and operational challenges. Unique Contribution to Theory, Practice and Policy: Based on these results, the study provides actionable recommendations for both policy formulation and management practices, emphasizing the importance of fostering a culture that promotes strategic agility. This approach is expected to contribute to improved organizational performance, ensuring that real estate firms can remain competitive and adaptable in an increasingly complex business environment.